Restoring the patency of fallopian tubes using the transcervical selective hysterosalpingography methods - a clinical case analysis - Justyna Wójcik; Paulina Piotrowska; Aleksandra Obuchowska; Alicja Ozga; Anna Zych; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2019)
Abstract Introduction: Infertility caused by tubal occlusion is a relatively frequent affliction among women of child-bearing age. A common cause of tubal occlusion are mucous plugs accumulated inside the fallopian tubes, which results in blocking them. Selective hysterosalpingography (SHSG) is a method of removing the obstruction located in a proximal section of the fallopian tube. The most serious complication developed from this procedure is a fallopian tube perforation, however, it affects less than 1% of patients who undergo the treatment. The clinical success of recanalization of the fallopian tubes is estimated at about 85-88% and the frequency of successful pregnancies after the treatment is about 27%. Aim: To show the usage and effectiveness of SHSG in diagnosis and treatment in the obstruction of proximal section of fallopian tube. Case report: The patient, 33 years old, diagnosed with primary infertility, qualified to the SHSG at Independent Public Clinical Hospital No. 4 in Lublin. The first stage of SHSG was the insertion of a catheter into the uterine cavity and introduction of a contrast agent to the uterine cavity. The fallopian tubes did not release the contrast into the peritoneal cavity. After increasing the contrast, delivery pressure agent obtained the free flow of the contrast agent into the peritoneal cavity through the right fallopian tube. The uterine outlet of the left fallopian tube was selectively catheterized and a micro tool was inserted into the left fallopian tube. As the result, both fallopian tubes were unblocked. Summary: SHSG is a non-invasive and safe method of removing the obstruction located in the proximal section of the fallopian tube. Women subjected to SHSG can return to their normal activities in a few hours after treatment.